Experiencing Event Management During the Coronavirus Pandemic: A Public Sector Perspective - Coles, Tim; Garcia, Giselle; O'Malley, Evelyn; Turner, Cathy (Frontiers in Sports and Active Living, 2022)
Events have played a significant role in the way in which the Coronavirus pandemic has been experienced and known around the world. Little is known though about how the pandemic has impacted on supporting, managing and governing events in municipal (i.e. local) authorities as key stakeholders, nor how events have featured in the opening-up of localities. This paper reports on empirical research with senior events officers for local authorities in the UK on these key knowledge gaps. Specifically, it examines events officers' unfolding experiences of the pandemic. The paper points to unpreparedness for a crisis of this scale and magnitude and the roles of innovation, adaptation and co-production in the emergent response. It highlights the transformative nature of the pandemic through reconsiderations of the purpose of public sector involvement in events and, from a policy perspective, how relatively smaller-scale, more agile and lower-risk arts events and performances can figure in local recovery. Finally, while the effects on, and response of, the body corporate (the local authority) to crises is an obvious focus, it is important to recognise those of the individuals who manage the response and drive change.